Tratamento das rupturas agudas do tendão calcâneo em atletas de futebol com utilização de concentrado de aspirado da medula óssea (BMAC) - Silva, Carlos Henrique Mendonça (2025)
The acute and complete rupture of the calcaneal tendon in soccer players is a catastrophic injury, which sidelines the athlete for a long period of their sports activity and, invariably, the athlete does not return to their pre-injury sports level and, in some cases, permanently interrupts their sports activity due to sequelae from the surgical treatment, which is currently the procedure of choice for treating this injury in soccer players. Preclinical and clinical studies have investigated the use of mesenchymal stem cells from bone marrow in tendon injuries and point out that the use of BMAC (bone marrow aspirate concentrate) may be a promising alternative in the treatment of tendon injuries, potentially resulting in significant improvement in tissue repair and functional recovery when compared to conventional treatment methods. The objective of this work was to evaluate the results of the repair of acute and complete ruptures of the calcaneal tendon in football athletes, with the application of BMAC, through sequential magnetic resonance imaging exams. All six patients showed complete healing of the lesions in twelve weeks, as confirmed by the magnetic resonance exams. There were no significant complications during the entire treatment. The functional recovery of the athletes was effective, allowing them to return to sports activities within sixteen weeks without complications. Treatment with BMAC proved to be reproducible, effective, safe, and easy to perform in the cases conducted, with promising results as an alternative to conventional surgical treatment. Studies with strong evidence and good methodologies should be conducted to confirm the real potential of cell therapies using BMAC and its possible advantages compared to other treatment options